(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the concept of technocivilization and its formation, as well as the socio-cultural transformations brought about by technological progress from a philosophical perspective. The author analyzes how technology is reshaping human life, values, and thinking within the framework of modern society.